MAFIC INCLUSIONS (SOBSKY COMPLEX, POLAR URAL): U‐Pb (SIMS) DATA - О. V. Udoratina; М. A. Coble; A. S. Shuyskiy; V. A. Kapitanova (Геодинамика и тектонофизика)
The rocks of the Sobsky complex, composing the bulk of the Sobsky batholith in the Polar Urals, contain mafic inclusions. The geological, petrographic and petro‐geochemical data show that the mafic inclusions of the Sobsky rocks belong to igneous formations, which are similar in their characteristics to autoliths. According to all the characteristics, these are the structures non‐contrasting to host rocks and having different structural‐textural features, a more basic composition of minerals and a more basic composition of rocks. The contact with the rocks of the complex is sharp and clear. The rocks of the complex in contact with autoliths are medium‐grained massive diorite rocks, quartz diorites, tonalites, mafic inclusions rocks – fine‐grained gabbros, gabbro‐diorites, and diorites. Isotopicgeochemical (U‐Pb, SIMS) data on zircons from the mafic inclusions suggest that their age is close, within the error limits, to the age of zircons from the enclosing Sobsky complex rocks.